Consequences of Domestic Violence against Women Referred to Health Centers in Zanjan: Qualitative Research - Ebrahimi, Loghman; Mohamadlou,Maryam (Zanjan University of Medical Sciences and Health Services, 2019)
Background: The World Health Organization has declared domestic violence against women as an important health priority. Objectives: This study aimed to identify the psychological, familial, and social consequences of domestic violence against women who referred to health centers in Zanjan province. Methods: The present study was conducted using a qualitative approach and the grounded theory method. In addition, the purposeful sampling technique was performed among married women who were subjected to violence and referred to the health centers of Zanjan province in 2019. Data were collected through semistructured interviews and analyzed by thematic analysis. Results: Domestic violence against women in different dimensions including emotional problems, biological problems and psychological trauma, emotional divorce, children's problems, economic violence, verbal and physical violence, the lack of support, social rejection, and social incompatibility had devastating effects on the psychological, family, and social status of women. Conclusion: Considering the destructive effects of domestic violence against women, taking serious measures is necessary regarding preventing and reducing these consequences through psychological interventions, educational programs, and counseling for families exposed to violence. Finally, pre-marital workshops should further be provided for young couples by relevant institutions.